Norovirus Recombinant Strains Isolated from Gastroenteritis Outbreaks in Southern Brazil, 2004-2011. - Tulio Machado Fumian; Juliana da Silva Ribeiro de Andrade; José Paulo Gagliardi Leite; Marize Pereira Miagostovich (PLoS ONE, 2016)
Noroviruses are recognized as one of the leading causes of viral acute gastroenteritis, responsible for almost 50% of acute gastroenteritis outbreaks worldwide. The positive single-strand RNA genome of noroviruses presents a high mutation rate and these viruses are constantly evolving by nucleotide mutation and genome recombination. Norovirus recombinant strains have been detected as causing acute gastroenteritis outbreaks in several countries. However, in Brazil, only one report of a norovirus recombinant strain (GII.P7/GII.20) has been described in the northern region so far. For this study, 38 norovirus strains representative of outbreaks, 11 GII.4 and 27 non-GII.4, were randomly selected and amplified at the ORF1/ORF2 junction. Genetic recombination was identified by constructing phylogenetic trees of the polymerase and capsid genes, and further SimPlot and Bootscan analysis of the ORF1/ORF2 overlap. Sequence analysis revealed that 23 out of 27 (85%) non-GII.4 noroviruses were recombinant strains, characterized as: GII.P7/GII.6 (n = 9); GIIP.g/GII.12 (n = 4); GII.P16/GII.3 (n = 4); GII.Pe/GII.17 (n = 2); GII.P7/GII.14 (n = 1); GII.P13/GII.17 (n = 1); GII.P21/GII.3 (n = 1); and GII.P21/GII.13 (n = 1). On the other hand, among the GII.4 variants analyzed (Den Haag_2006b and New Orleans_2009) no recombination was observed. These data revealed the great diversity of norovirus recombinant strains associated with outbreaks, and describe for the first time these recombinant types circulating in Brazil. Our results obtained in southern Brazil corroborate the previous report for the northern region, demonstrating that norovirus recombinant strains are circulating more frequently than we expected. In addition, these results emphasize the relevance of including ORF1/ORF2-based analysis in surveillance studies as well as the importance of characterizing strains from other Brazilian regions to obtain epidemiological data for norovirus recombinant strains circulating in the country.